IMPLEMENTASI ASESMEN PENDIDIKAN AGAMA ISLAM DI SDN RINGINSARI - Evi Sulfaningsih; Muhammad Zaki Ridho Djakfar; Siti Sahra; Adisti Anggraini; Izzadheva Ratu Haramain; Nurhidayat; Retno Try Purnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of assessment in Islamic Religious Education (PAI) learning at SDN Ringinsari, covering the stages of planning, implementation, processing and reporting of assessment results, as well as reflection and follow-up. The research employed a descriptive qualitative approach with the Islamic Religious Education teacher as the main informant selected through purposive sampling. Data were collected through observations, interviews, and documentation, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the assessment process has generally been implemented in accordance with the principles of the Merdeka Curriculum. Teachers have designed assessments based on learning objectives and utilized diagnostic, formative, and summative assessments supported by digital media such as Quizizz and Kahoot. The processing and reporting of assessment results were conducted through e-Rapor and supported by Microsoft Excel as backup documentation. In addition, teachers carried out reflective practices and follow-up actions through remedial and enrichment programs. However, several challenges remain, particularly in implementing differentiated and authentic assessments for students with diverse learning needs. Therefore, optimization is still needed in developing more systematic assessment instruments, holistic reporting, and adaptive follow-up strategies to improve the quality of Islamic Religious Education learning sustainably.